2019
DOI: 10.4048/jbc.2019.22.e7
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Breast Reconstruction Does Not Have a Clinically Significant Impact on Adjuvant Treatment Delay and Subsequent Survival Outcomes

Abstract: Purpose The use of immediate breast reconstruction (IBR) has been debated because it may be a causative factor in adjuvant treatment delay and may subsequently increase the probability of recurrence. We investigated whether IBR was related to adjuvant treatment delay and survival outcomes. Methods We retrospectively analyzed the duration from operation to adjuvant treatment administration and survival outcomes according to IBR status among patients with breast cancer wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
(31 reference statements)
1
19
2
1
Order By: Relevance
“…Several studies have demonstrated oncologic safety in the patients who underwent IR following mastectomy [ 14 16 ]. In addition, the majority of previous studies on the impact of chemotherapy or radiotherapy on postoperative complications after immediate breast reconstruction reported that chemotherapy or radiotherapy did not increase postoperative complications and immediate breast reconstruction did not affect the initiation of adjuvant treatment [ 5 , 8 11 , 17 24 ]. This study also reported that chemotherapy or radiotherapy did not affect postoperative complications in the patients who underwent immediate breast reconstruction with tissue expander.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated oncologic safety in the patients who underwent IR following mastectomy [ 14 16 ]. In addition, the majority of previous studies on the impact of chemotherapy or radiotherapy on postoperative complications after immediate breast reconstruction reported that chemotherapy or radiotherapy did not increase postoperative complications and immediate breast reconstruction did not affect the initiation of adjuvant treatment [ 5 , 8 11 , 17 24 ]. This study also reported that chemotherapy or radiotherapy did not affect postoperative complications in the patients who underwent immediate breast reconstruction with tissue expander.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated oncologic safety in the patients who underwent IR following mastectomy [11][12][13]. In addition, the majority of previous studies on the impact of chemotherapy or radiotherapy on postoperative complications after immediate breast reconstruction reported that chemotherapy or radiotherapy did not increase postoperative complications and immediate breast reconstruction did not affect the initiation of adjuvant treatment [3,[7][8][9][10][14][15][16][17][18][19][20][21]. This study also reported that chemotherapy or radiotherapy did not affect postoperative complications in the patients who underwent immediate breast reconstruction with tissue expander.…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction after mastectomy has a positive impact on patients' psychosocial and sexual wellbeing. Moreover, immediate breast reconstruction can provide patients with the opportunity to reduce one additional surgery and costs instead of undergoing two separate procedures [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated oncologic safety in the patients who underwent IR following mastectomy [15][16][17]. In addition, the majority of previous studies on the impact of chemotherapy or radiotherapy on postoperative complications after immediate breast reconstruction reported that chemotherapy or radiotherapy did not increase postoperative complications and immediate breast reconstruction did not affect the initiation of adjuvant treatment [5,[9][10][11][12][18][19][20][21][22][23][24][25]. This study also reported that chemotherapy or radiotherapy did not affect postoperative complications in the patients who underwent immediate breast reconstruction with tissue expander.…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction after mastectomy has a positive impact on patients' psychosocial and sexual well-being. Moreover, immediate breast reconstruction can provide patients with the opportunity to reduce one additional surgery and costs instead of undergoing two separate procedures [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%